Use of raw soybeans in sow diets - Allee, G.L.; Li, De-Fa; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy-six gilts were used to evaluate the effects of feeding raw soybeans during gestation, lactation, and rebreeding on sow and litter performance. Reproductive performance during two parities was not impaired by feeding raw soybeans. However, sows fed raw soybeans lost more weight during lactation than sows fed soybean meal. The factor (or factors) responsible for this increased weight loss during lactation and the long-term consequences remains to be determined.
Keywords: Swine; Raw soybeans; Diets